PRINSIP KEADILAN DALAM TANGGUNG JAWAB NEGARA TERHADAP KORBAN TINDAK PIDANA KARENA PELAKU TIDAK MENJALANI PEMIDANAAN - Meldy Ance Almendo (Yuridika, 2016)
In the expansion of its objectives a convicted must also pay attention to justice for victims. The principle of equality before the law should be applied as equal justice for the perpetrators and for the victims. If the state takes over the enforcement of the criminal law because the mandate of the victim as a citizen of the state, the state shall be liable to the victim. This paper will discuss, the philosophical foundations of the State's responsibility to victims of crime, the principle of justice in the form of state responsibility to the victim as a result of failure of the responsibility of the offender conducting the sentence. Due to legal science has characteristics that are percriptive so this study, using normative legal research (doctrinal) is the research to produce arguments, theories or new concepts as prescriptions in solving the problems faced.